Between the Reality and the Regulation of Land Ownership Transfer Services by Buying and Selling at the Land Office - Tiffany Heruveradita; Yaqub Cikusin; Slamet Muchsin (Universitas Muhammadiyah Gorontalo, 2022)
This research attempts to ascertain how service rules for the purchase and sale of land ownership rights are implemented and to explain the difficulties encountered while enforcing legislation. The implementation model theoretical reference from van Metter & van Horn is utilized to tackle this issue. Data collecting methods included observation, document analysis, and interviewing. Using interactive model analysis procedures that include data reduction, data display, and conclusions, the data was examined. Interviews, observation, and document analysis are all employed in the data collecting process. This analysis demonstrates that while the adoption of the rule has followed the proper procedures, the timeliness of service is still far behind expectations. This is because there are many application files, which means that the workload is more than the capacity of the available human resources, the application files are incomplete, the applicant's ID has not been verified, and there are no supervising or executor officials in place.